Spontaneous mammary carcinomas in female dogs: association between the immunohistochemical degree of aggressiveness of tumors, intensity of DNA damage and residues of pyrethroids - Brandão, Yara de Oliveira [UNESP]; Colodel, Marcia Moleta [UNESP]; Silva, Glenda Nicioli da [UNESP]; Vexenat, Stephane Cássia [UNESP]; Ferreira, Isabelle; Silva, Yamê Fabres Robaina Sancler da [UNESP]; Bulla, Camilo; Rocha, Noeme Sousa [UNESP] (My University, 2013)
Diagnosis and biological behavior of breast cancer of female dog represent one of the biggest challenges facing the Veterinarian in recent years. Due to its exponential growth and the degree of aggressiveness, the exact cause of this tumor is probably multifactorial and it is believed that may suffer influence from environmental factors. Among the suspected environmental contaminants are the pyrethroids. Aiming to investigate the participation of pyrethroids in tumorigenesis in female dogs, a study was conducted using 50 female dogs, 22 were positive for simple breast carcinoma (Group I), 18 with a diagnosis of complex breast carcinoma (Group II) and 10 negative (Group III) for breast cancer. In order to detect DNA damage, the Comet assay was performed on mammary samples of these animals, which also had samples submitted to the technique of High Performance Liquid Chromatography (HPLC), which aimed to quantify the concentration of pyrethroids. The results of HPLC of each animal were compared with those obtained by the Comet assay analysis of variance and the means were compared by the test groups “Student T” at the significance level of p  0.05. Despite presenting correlation between the amount of DNA damage and tumor aggressiveness, no statistical differences were found in the DNA damage of different histologic types of breast carcinoma. As for pyrethroids, even these were detected in 22% of tumor tissues and peritumoral fat, there was no difference in DNA damage between cells exposed and not exposed to environmental contaminant.
Keywords: Mammary; Carcinomas; DNA damage; Pyrethroids